Assessment of 112 tomato (Solanum lycopersicum L.) cultivars for industrial processing in Portoviejo, Ecuador (2018)
Tomato (Solanum lycopersicum L.) processing industry requires varieties with increased production and quality, and also with resistance to pest, in order for producers to cultivate these. The aim of this study was to carry out an evaluation of 112 tomato cultivars for production and quality characteristics from the following providers: Orsetti Seed, Heiz Seed, Ohio University, United Genetic and Harrys Moran. The experiment was conducted at the Experimental Research Station Portoviejo of INIAP. Statistical analyses used were principal components analysis for a group of 112 cultivars based on production parameter: yield (t.ha-1), average fruit weight (g), number of fruits per plant, defective fruits per plant; in addition to quality parameters as: brix degrees, pH, and acidity. Data were analyzed through an analysis of variance and a Tukey test to establish statistical differences and significance ranges among industrial tomatoes. Results showed that ca. 9 % of the total tomato varieties assessed showed superior characteristics. Five statistical significance ranges were detected, where the first three were materials developed by Ohio University. The best material evaluated was the cultivar SG 07-627, and all materials showed diverse resistance to pests, with potential for genetic breeding as part of an integral pest management strategy for tomato.